Tinjauan Aspek Bentuk dan Fungsi Display Bola Aroma pada Interior Rumah Atsiri - Sari, Sely Novia; Isfiaty, Tiara (Waca Cipta Ruang, 2021)
Aroma Ball Interior display design at Rumah Atsiri Indonesia is one of the most important parts that has become a medium of reciprocal action between visitors and the objects on display. Rumah Atsiri Indonesia is an edu-recreational place for various essential plant fragrances. This essential plant is processed into essential oils that can later be enjoyed by various societies. At Rumah Atsiri Indonesia, there is a museum tour agenda. At the museum there is a unique room where a display shaped like water balls. The room is called the Aroma Ball Room. Aroma Ball Room stores and releases some extraordinary aromas of various types of essential oils. Visitors are spoiled with a sensory experience of smell through aroma cruising. The shape of the alleged scent ball display can counterbalance the outside air with the aroma centered on the aroma ball display. One of the showrooms is located in Karanganyar Jawa Tengan by offering its visitors to relieve stress through essential oil plants. This research uses a method of literature study research or literature study that involves theories applicable to these research problems with literature data in the Aroma Ball Room of Rumah Atsiri Indonesia.